PENGEMBANGAN MODUL ELEKTRONIK BERBASIS KETERAMPILAN BERPIKIR KREATIF MENGGUNAKAN 3D PAGE FLIP PROFESSIONAL PADA MATERI HIDROKARBON - Fitria, Rani; Nurhamidah; Handayani, Dewi (University of Bengkulu, 2024)
This study aimed to determine the feasibility level of, students’ response, level of students’ understanding of the electronic module based on creative thinking skills using 3D Page Flip Professional on Hydrocarbon subject at SMAIT IQRA'Bengkulu City. This type of research is R&D (Research and Development) which used 3 of the 4 stages of the 4D (Four D) development model included Define, Design and Development. The data of this study were obtained from a validation questionnaire from material and media experts, the results of small-scale trials, large-scale trial results, student response questionnaires and students' level of understanding of the developed electronic module. The feasibility level of the electronic module is based on material expert validation of 93.18% which states that the quality of the material in the electronic module is feasible from the material aspect and based on creative thinking skills, the validation of media experts is 97.20% which states that the display quality on the electronic module is appropriate from the media aspect, the small scale trial was 92.47% which stated that the discourse on the was easy to understand. Students’ response to the module in the field implementation test was 93.92% which stated that students gave a very good response to the developed electronic module and the level of student understanding based on the N-Gain Score of 0.37 was in the medium category. This showed that the electronic module based on creative thinking skills using 3D Page Flip Professional on hydrocarbon subject is very suitable to be used as teaching material in the learning process.